„halb und halb“ – Hybride Edition als Kompromiss? Eine Studie zu Methodik, Möglichkeiten und Grenzen in der hybriden Musikedition am Beispiel der Edition von Ludwig Baumanns „Kantate. Den Gefallenen zum Gedächtnis, den Trauernden zum Trost“ - Ried, Dennis
Vor etwa 20 Jahren haben hybride Editionen in der Musikwissenschaft Einzug gehalten. Es sind in erster Linie Langzeitprojekte mit Laufzeiten von über 15 Jahren (z. ,B. OPERA, RWA, EWK, BAZ-GA) die diese Form der Edition verwenden. Dennoch gibt es kaum Forschungsliteratur zu diesem Thema. Auch die immer wieder verwendete Forschungssoftware "Edirom" hat bislang weder eine ausreichende Dokumentation erfahren noch ist sie ausgiebig diskutiert worden. Zudem fehlt eine kritische Betrachtung des Phänomens Önline-Portal", welches gerade in der Musikphilologie immer häufiger in Erscheinung tritt. Von der Frage ausgehend, ob die hybride Edition ein Kompromiss aus traditioneller und digitaler Edition darstellt, unternimmt Dennis Ried erstmals den Versuch, den Status quo hybrider (Musik-)Editionen zu eruieren, zu dokumentieren und kritisch zu hinterfragen. "Hybrid" wird dabei stets als Zusammenspiel von Änalogem" und "Digitalem" betrachtet. Anders als traditionelle Dissertationsschriften ist diese Arbeit in zwei Teile gegliedert, wovon der erste aus einer exemplarisch angeführten und quasi eigenständigen wissenschaftlich-kritischen Edition besteht. Im zweiten Teil wird diese dann aktiv in die Theoriebildung eingebunden, um methodische Fragen gezielt erörtern zu können. Ergänzt wird die Dissertationsschrift durch eine auf Zenodo publizierte digitale Datensammlung.
Keywords: Musikwissenschaft; Digitale Edition; Musikphilologie

HenDi-Data (data package) v6.1.0 - Minetti, Elena; Capelle, Irmlind; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

HenDi-ODD v6.1.0 - Ried, Dennis; Capelle, Irmlind; Minetti, Elena

Edirom/WeGA-ODD: WeGA ODD files release 4.7.0 - Stadler, Peter; Anna Maria, Neubert; Schreiter, Solveig; Obert, Salome; Ried, Dennis

»Play it again, Sam« – Levels of Complexity in Encoding Performance Personnel - Bohl, Benjamin W.; Ried, Dennis (Music Encoding Conference Proceedings 2022)

Ludwig Baumann - Ried, Dennis (Blick in die Geschichte. Karlsruher stadthistorische Beiträge)

HenDi-ODD v2.0.0 - Ried, Dennis; Capelle, Irmlind; Minetti, Elena

HenDi-WebApp v1.0.0 - Ried, Dennis

HenDi-ODD v1.0.0 - Ried, Dennis; Capelle, Irmlind; Minetti, Elena

HenDi-WebApp v2.0.0 - Ried, Dennis

HenDi-Data (data package) v2.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

HenDi-Data (data package) v1.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

METAdata and metaDATA - Ried, Dennis; Gubsch, Clemens
Metadata are a very broad and extremely differentiated subject and ranges from rudimentary catalog data to deeply indexed scientific catalogs (e.g., catalogs of works). In this paper, the concept of metadata in the context of MEI is first examined, before two examples are used to show that metadata are more than just rudimentary descriptions. These examples are also intended to illustrate the extent to which metadata are encoded in the field of music philology and thus represent an attempt to create a little more awareness for the work of the Metadata and Cataloging Interest Group of MEI. The examples deal on the one hand with the encoding of performance resources and on the other hand with watermarks. In both cases, the possibilities of metadata encoding with MEI version 4 are exhausted and it is discussed which steps are useful and necessary to create an even deeper, machine-readable structure so that these sub-fields of the MEI metadata can also be used for larger scientific purposes such as analyses.

Weltweite Verfügbarkeit und digitale Langzeitarchivierung - Ried, Dennis (Mitteilungen der IMRG)

Musikalische Schrift und Digitalität. Ein Werkstattbericht - Freund, Julia; Muennich, Stefan; Ried, Dennis; Ziegler, Michelle

Lieder II

Der Liebe will ich singen. Hermann Reutters Begegnung mit dem Mittelalter - Ried, Dennis (Ritter, Tod und Teufel. Hermann Reutter und das Lied)

Erhebung, Transformation und Präsentation digitaler Forschungsdaten - Ried, Dennis (Brückenschläge zwischen Musikwissenschaft und Informatik. Theoretische und praktische Aspekte der Kooperation)
The process of data acquisition and transformation of Baumann Digital and Joachim-Raff-Archiv is the subject of this poster description. The data in both projects is (meanwhile) based on TEI and MEI to obtain a machine-readable corpus. The presentation platform created for this project was initially intended as a simple form of visualization for internal use, i. e. for structuring, proofreading of digital contents and first evaluations. The xQuery-based application for eXist-db was developed in detail during the first period of the Baumann Digital project, adding the dimension of public presentation to its original purpose. This poster focuses on the process of collecting, transforming and presenting the data of these two small projects, which have different research interests but deal with similar archival material.

[Vorwort] - Ried, Dennis (Welt-Ende, Gericht, neue Welt : Oratorium nach Worten der heiligen Schrift zumal der Offenbarung Johannis : op. 212 / Joachim Raff)

»auch auf gesanglichem Gebiete überaus thätig«. Max Reger und das Lied - Ried, Dennis (Musik in Baden-Württemberg. Jahrbuch 2019/20)